Spawning and growth of three species of threadfin breams off Madras - Vivekanandan, E (Indian Journal of Fisheries, 2011)
Considering the impcmtuice of threadfin l»«ams, Vivdcan&nilui and Junes (1986) studied the spawning, growth »id peculation dymunics otNemiptermjaponicus in the trawluig grounds off Madras. As a continuation of this study, the owning and growth of 3 other qxciesof dueadfln breams, viz.M mesoprion (Bleek^), N. tolu (Valenciennes) and N. delagoae Smith, were studied. The results obained during the study are presented in this paper.